Heat stress and soil thermal gradients shape root-associated fungal community recruitment - Catarecha, Pablo; King, Eoghan; Díaz-González, Sandra; Caro, Elena; Sacristán, Soledad; del Pozo, Juan Carlos (Frontiers in Microbiology, 2025)
Climate change is increasing the overall temperature of the planet and increasing the number of extreme heat waves events. These phenomena are negatively affecting crop production and food security. Thus, under this scenario, understanding the adaptations that encompass the plant response to high temperature will be essential to enhance crop tolerance and yield. Plant responses to elevated temperature rely on both genetic factors and the dynamic interplay with the surrounding microbiota. Recently, the role of root microbiota as a key player in the plant’s response to heat, is gaining significant relevance. This work presents the analysis of fungal microbiota from the rhizosphere and the root-associated fractions of tomato roots in response to high temperature. Although the analyses were done in an enclosed environment, we used the TGRooZ (Temperature Gradient Root Zone) system to mimic field conditions. The TGRooZ generates a temperature gradient like the natural soil during a heat wave event. We found that distinct soil/root compartments assemble a different fungal community, with the rhizosphere fraction exhibiting greater diversity and abundance, while the root-associated fraction was enriched in fewer but more specialized taxa. Notably, the experimental conditions used to analyze heat responses significantly influenced the final microbiome composition. Our data suggest that the TGRooZ system will enable more accurate analysis of plant-microbiome responses to heat stress and help evaluate the potential of beneficial microbes to enhance crop productivity under near-natural conditions.